Advances in Surface Materials for Resisting Snow and Freezing Disasters - Wu, Xin-Nuo; Zhao, Xue-Ying; Liu, Jie (Chinese journal of polymer science, 2025)
Snow and freezing disasters are recurrent weather and climate phenomena that affect the world annually. These events exert a significant influence on numerous aspects of life, including transportation, power supply, and daily activities, and result in considerable economic losses. This study aims to provide a comprehensive analysis of the regions affected by these disasters, the preventive and responsive measures employed, recent advancements in key materials, and the challenges encountered. By doing so, we can gain a deeper understanding of the vital role, significant advantages, and untapped potential of key materials for effectively preventing and responding to snow and freezing disasters. Furthermore, promoting research and utilization of these materials not only contributes to the development of the safety and emergency equipment industry but also strengthens the supply of advanced and suitable safety and emergency equipment.